TINJAUAN YURIDIS PERSEROAN TERBATAS DAN RAPAT UMUM PEMEGANG SAHAM - Sri Agustini (Ensiklopedia of Journal, 2021)
One thing that must be ascertained is whether the debt transaction for renting the house is carried out on behalf of the Limited Company (PT) in question or not. The problem you are asking is easier to understand if the context of the answer to that question is that the transaction is carried out on behalf of PT. Taking into account the above, it is likely that the transaction is a transaction relating to the facilities of the members of the Board of Directors and the Board of Commissioners. By taking into account the context on behalf of the PT, the legitimacy of the above transactions does not only cover the formal aspects (complete fulfillment of the provisions of the Articles of Association by the Board of Directors as representatives of the PT and/or corporate approval) but also concerns the material aspects (seeing whether the personal interests of the Board of Directors or Commissioners conflict with interests/intentions and objectives of PT). This is based on the fact that a PT can act if there is an individual who runs it, in this case the Board of Directors as management. In the event that: (i) it turns out that the Board of Directors representing the PT is legitimate from the formal and material aspects, and (ii) it turns out that the circumstances in which each member of the Board of Directors or Commissioners has the right to receive the above facilities have been regulated in the Company Regulations of the PT, and (iii) it turns out that as an entity The PT has not paid the lease debt, then the PT is the one who fully bears the lease debt regardless of whether or not there is a replacement or change in the composition of the members of the Board of Directors or the Board of Commissioners. On the other hand, the PT is not responsible for the actions of the Board of Directors which, although formally on behalf of the PT, have materially proven to be contrary to or outside the interests of PT. Shareholders should not receive the same facilities because they do not function as management (Directors; in Article 79 UUPT) or supervisors (Commissioners; in Article 97 UUPT) of the PT, but as capital holders (investors) who expect profits/benefits from the acquisition. dividend distribution. Even if there is such a transaction through PT and a third party, then the transaction is a special relationship transaction whose fairness assessment tends to be more of a concern according to the applicable accounting standards. If the PT wants to bear indirectly, then the type of transaction should also be a loan to shareholders. If it is a material transaction, then the shareholder in connection with the PT's actions against a third party may also be personally liable in the event that his/her actions regarding the transaction meet one of the criteria (stipulations) of Article 3 Paragraph (2) of Law Number 40 of 2007 concerning Limited Liability Companies. So, transactions that are not on behalf of the PT are definitely the personal responsibility of each member of the Board of Directors or CommissionersKeywords: Limited Liability Company, General Meeting of Shareholders